Something in need is something indeed - Zhou, Caicun; Manegold, Christian; Song, Yong (Translational Lung Cancer Research; Vol 1, No 1 (March 18, 2012): Translational Lung Cancer Research, 2012)
The new year of 2012 is doomed to be the one with miraculous stories. One of them, as we are honored to announce, is the launch of Translational Lung Cancer Research (TLCR), the first journal of its scope and coverage in world, with the strong support and active involvement of our editorial members and colleague investigators in biomedical research and clinical practices of lung cancer.